Geo-Environment Aspects Assessment Applied In Land Stability Determination Of A Disaster-Prone Area: A Case Study Around The Lembang Active Fault Zone, On The Western Part Of Bandung Basin, Indonesia - Iskandarsyah, Teuku Yan Waliana Muda; Brilian, Ciria Humanis; Trisnadiansyah, Mochamad Ridfan; Listiawan, Yudhi; Barkah, M. Nursiyam; Sulaksana, Nana; Hendarmawan, Hendarmawan (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
Rainfall, landforms, lithology or soil characteristics, and geological structures are geo-environment aspects that might be used to assess stability of the land in a disaster-prone area, e.g. in a case of study around the Lembang active fault zone of the western part of Bandung Basin, Indonesia. In this study, such geo-environment aspects were weighted and scored constantly in five class of value and importance, due to its influence on the land stability. After this scoring method applied, firstly, a land capability of the research area in relation to disaster potential will be recognized and used to analyze its land stability. According to such analyses, the study area can be divided into two zones of land stability, i.e. (i) moderate area which dominates the research area, and (ii) non-stable or unstable area near Lembang active fault zone. The dominant moderate and unstable area show that the fault zone has still widely affected the surroundings landscape and its physical characteristics. In fact, the current evaluation of existing landuse show that the development has been carried out intensively on these areas. It indicates that the development of the area is contituted as a high risk activity. Therefore, in this case, a good spatial planning or an environmental good governance must be applied appropriately in such disaster-prone area.